Conditions to improve controls for certification of Sardinian PDO cheeses - Piredda G.; Scintu M.F.; Ledda A. (L'évolution des systèmes de production ovine et caprine : avenir des systèmes extensifs face aux changements de la société, 2004)
In Sardinia, three Protection of Designation of Origin (PDO) cheeses, Pecorino Romano, Pecorino Sardo and Fiore Sardo are produced from ewes' milk. The factories range from medium size industrial plants for the two Pecorinos, to small farms where shepherds manufacture Fiore Sardo. In order to respect the Council Regulation (EEC) No. 2081/92 of 14/07/92 and to reduce management costs, cheese producers created a new certification structure named 'Organismo di Controllo delle Produzioni Animali' (OCPA). It was founded by the consortiums for the protection of the three cheeses, in collaboration with 'Istituto Zootecnico e Caseario per la Sardegna' and 'Ente Regionale di Sviluppo e Assistenza Tecnica in Agricoltura'. In respect to the principles of the Standard EN45011, the OCPA management is separated from the certification activity and every action to reach the certification is documented. The first results of the OCPA certification are positive, contributing to the development of Sardinian farms.
Séminaire du Sous-Réseau Systèmes de Production du Réseau Coopératif Interrégional FAO-CIHEAM de Recherche et Développement sur les Ovins et les Caprins, 2002/04/04-06, Alghero (Italy)